Ар-деко и стилевой параллелизм в архитектуре 1930-х - Barkhin, Andrei (проект байкал, 2019)
Stylistic variety in architecture of the 1930s is demonstrated by the key achievements of the Art Deco style: pavilions of the 1925 Paris Exhibition, high-rises built in the late 1920-s – early 1930s in American cities. There was a diversity of historical sources of the style. However, Art Deco represents comprehensive and recognizable aesthetics. Its examples can be found in the Soviet architectural heritage of the 1930s. Art Deco is a world architectural trend of the interwar period. The article describes the phenomenon of stylistic parallelism in the national and foreign architecture of the 1930s.